Zirconium in the Nuclear Industry: 17th Volume 2014
DOI: 10.1520/stp154320120215
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Alloying Elements on Hydrogen Pickup in Zirconium Alloys

Abstract: Although the optimization of zirconium-based alloys has led to significant improvements in hydrogen pickup and corrosion resistance, the mechanisms by which such alloy improvements occur are still not well understood. In an effort to understand such mechanisms, we conducted a systematic study of the alloy effect on hydrogen pickup, using advanced characterization techniques to rationalize precise measurements of hydrogen pickup. The hydrogen pickup fraction was accurately measured for a specially designed set … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 59 publications
0
10
0
Order By: Relevance
“…The oxidation of SPPs [e.g., Zr(Cr,Fe) 2 in Zircaloy-4, β-Nb and ZrNbFe precipitates in ZIRLO] is delayed relative to that of the Zr matrix so that the precipitates are initially incorporated in metallic form into the oxide layer. This delayed oxidation of alloying elements incorporated into the oxide layer has been verified by TEM (78)(79)(80), by X-ray absorption near-edge spectroscopy (XANES) (81)(82)(83), and more recently by μ-XANES (29,84). As the oxide advances further, the alloying elements in these precipitates eventually become oxidized; the delay is proportional to the tendency of elements to oxidize as specified by Ellingham's or Pourbaix diagrams.…”
Section: Second-phase Precipitatesmentioning
confidence: 84%
“…The oxidation of SPPs [e.g., Zr(Cr,Fe) 2 in Zircaloy-4, β-Nb and ZrNbFe precipitates in ZIRLO] is delayed relative to that of the Zr matrix so that the precipitates are initially incorporated in metallic form into the oxide layer. This delayed oxidation of alloying elements incorporated into the oxide layer has been verified by TEM (78)(79)(80), by X-ray absorption near-edge spectroscopy (XANES) (81)(82)(83), and more recently by μ-XANES (29,84). As the oxide advances further, the alloying elements in these precipitates eventually become oxidized; the delay is proportional to the tendency of elements to oxidize as specified by Ellingham's or Pourbaix diagrams.…”
Section: Second-phase Precipitatesmentioning
confidence: 84%
“…The Zr alloys of choice in most current water-cooled reactor designs con-M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT tain 0.5-2.5 wt. % Nb due to its beneficial effect on HPUF [5,6,7]. Long term autoclave studies have demonstrated that Zr-2.5Nb exhibits near parabolic corrosion kinetics, and a lower corrosion rate than other Zr-based alloys such as Zircaloy-4 and Sn-containing alloys such as ZIRLO, as shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Corrosion of Zry-4, ZIRLO and Zr-2.5%Nb at 360°C in de-ionised water under saturated pressure conditions at 18.7 MPa, reproduced from[7].…”
mentioning
confidence: 99%
“…It has been demonstrated that alloys with a more electrically conductive oxide layer exhibit a lower HPUF [14]. This allows electrons to move more freely though the oxide and thus allows hydrogen ion/electron recombination to occur further from the metal/oxide interface, which consequently reduces the probability of the hydrogen reaching the cladding metal [15].…”
Section: Introductionmentioning
confidence: 99%